Long non‐coding RNAs in aging organs and tissues. (25th October 2017) - Xing, Wenmin; Gao, Wenyan; Mao, Genxiang; Zhang, Jing; Lv, Xiaoling; Wang, Guofu; Yan, Jing
Summary: The aging process directly impacts bodily functions on multiple levels, including a reduced ability to resist stress, damage and disease. Besides changes in metabolic control, the aging process coincides with the altered long non‐coding RNAs (lncRNAs) expression, which are ≥200nt long class of non‐protein coding RNAs. The majority of non‐coding transcripts of mammalian organs and tissues are expressed in developmentally regulated and cell‐type specific manners. Specific altered lncRNA level has been involved in induction and maintenance of the whole human body aging with highly specific spatial andtemporal expression patterns. Furthermore, many lncRNAs are transcribed in sense, antisense and bidirectional manners in the mammalian genome. They play a vital role in regulating organ or tissue differentiation during aging by binding with miRNA or proteins to act as a decoy. Recently, the correlation between lncRNAs and aging has been studied intensely. Here, we have summarized some examples of known and novel lncRNAs that have been implicated in the aging process in the whole mammalian body and we discuss these patterns, conservation and characters during aging. This may further promote the development of research on lncRNAs and the aging process.